Pemberdayaan Masyarakat RT 03 RW 05 di Kelurahan Langensari Kabupaten Semarang - Dionisia Mayola; Isri Nasifah; Lusiana Wiwit (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Family assessment practice (PPK) is one of the student activities that must be carried out where it is a real form of work in providing Community Midwifery Care Services, where community midwifery is one of the courses in the Community Midwifery Profession curriculum with the aim of implementing comprehensive Midwifery practice by paying attention to the culture of the community in the community setting with a midwifery management approach and based on the concept of professional skills and attitudes. During this Family Study Practice (PPK), it is hoped that the students of the Profession of Midwife at Ngudi Waluyo University will carry out community participation movements and overcome problems found in the family, so that families are able to help themselves in the health sector. After following the Family Assessment Practice (PPK) students are expected to be able to identify, plan, prioritize, implement, and evaluate community midwifery service management with community movement and empowerment techniques as well as educational approaches to individuals, families, special groups or in certain communities. In the implementation of this community midwifery practice, the assessment was carried out by means of direct interviews, and secondary data collection. After counseling and asking questions, the client already understands the danger signs in pregnancy. Cadres and Midwives are expected to be more active in providing health information to the public, especially pregnant women. AbstrakPraktik pengkajian Keluarga (PPK) merupakan salah satu kegiatan mahasiswa yang harus dilaksanakan dimana suatu bentuk kerja nyata dalam memberikan Pelayanan Asuhan Kebidanan Komunitas, dimana kebidanan komunitas ini merupakan salah satu mata kuliah dalam kurikulum Profesi Kebidanan Komunitas dengan tujuan melaksanakan praktik Kebidanan secara komperehensif dengan memperhatikan budaya masyarakat dalam tatanan di Komunitas dengan pendekatan manajemen kebidanan dan didasari oleh konsep keterampilan dan sikap Profesional. Selama Praktik pengkajian Keluarga (PPK) ini diharapkan mahasiswa Profesi Bidan Universitas Ngudi Waluyo, melakukan pergerakan peran serta masyarakat serta mengatasi masalah yang ditemukan pada keluarga, sehingga keluarga mampu menolong dirinya sendiri dalam bidang kesehatan. Setelah mengikuti Praktik pengkajian Keluarga (PPK) diharapkan mahasiswa mampu mengidentifikasi, merencanakan, memprioritaskan, mengimplementasikan, dan mengevaluasi manajemen pelayanan kebidanan komunitas dengan teknik pergerakan dan pemberdayaan masyarakat serta pendekatan edukasi pada individu, keluarga, kelompok khusus ataupun pada komunitas tertentu. Dalam pelaksanaan praktik kebidanan komunitas ini pengkajian dilakukan dengan cara wawancara langsung, dan pengambilan data sekunder. Setelah di lakukan penyuluhan dan dilakukan tanya jawab klien sudah mengerti tentang tanda bahaya dalam kehamilan. Diharapkan Kader dan Bidan lebih aktif memberikan informasi kesehatan kepada masyarakat khususnya pada ibu hamil.